Diabetes and Pancreatic Anastomosis: Friend or Foe? - Kafle, Awaj; Gupta, Vikas (Journal of College of Medical Sciences-Nepal, 2018)
Background & Objectives: Pancreaticoduodenectomy (PD) has become a standard operative procedure for both benign and malignant lesions of pancreatic head and periampullary region. Pancreatic Fistula (PF) is the most troublesome complication and heralds the development of other complications. The procedure was associated with high morbidity and mortality in the past but with the identification of various risk factors associated with the development of PF, the management has changed dramatically. Similarly, Diabetes mellitus (DM) and poor glycemic control is associated with various adverse postoperative events. So, the objective of this study was to identify the association between DM and postoperative occurrence of PF. Materials & Methods: This was a prospective cross-sectional study enrolling a total of 72 patients. Patients were screened for the presence or absence of DM based on guidelines by American Diabetes Association in January 2009. After surgery, patients were observed for the development of PF. The association between these two was assessed using Chi-Square test. Results: Out of 72 patients, 12 had DM. All the patients who had DM did not develop PF; in contrast 15 patients who developed PF were non-diabetic. Conclusion: Diabetes Mellitus was found to be protective in preventing the occurrence of PF postoperatively.